Synthesis of Signals with Zero Width of Autocorrelation Function - Velichko, A.P.; Mirsaitov, S.F.; Snedkov, A.B.; P.O. Shishkov, P.O. Shishkov (International Journal of Engineering and Technology, 2018)
This article presents examples of Â probing functions construction with a small width of autocorrelation function (a noise-like signal, a chirp signal) of long duration, which allows to obtain a reflectivity profile along a high resolution path. Attention is drawn to the fact that space in the process of probe pulse propagation returns to the receiver in an almost mutual correlation function of reflectivity and probe pulse. This approach opens up new possibilities for filtering signals and recognizing targets with appropriate selection and changing shape of the probe pulse right during measurements.